Comparative study of serum lipid profile between prehypertensive and normotensive - Jani, Hitesh A.; Bhanderi, Priti C.; Sharma, Chandankumar; Padalia, Maulik (International Journal of Research in Medical Sciences, 2017)
Background: Prehypertensive subjects have greater risk of developing hypertension than the normotensive subjects. Studies have shown that lipid profile is altered in hypertensive patients as compare to normotensive subjects. But not much is documented about lipid profile in prehypertensives. So the present study is done to compare the serum lipid profile among prehypertensive and normotensives and to correlate the blood pressure and lipid profile in prehypertensives. Methods: 50 prehypertensive and 50 normotensive subjects were recruited from the general population. Blood pressures were recorded and serum lipid profiles were measured and compare using student t test. Correlation of serum lipid profile and blood pressure was done using person correlation. Results: The study results showed significant increased in total cholesterol, LDL, VLDL and serum triglyceride level in prehypertensives compare to normotensives. While there is no significant change in HDL level in prehypertensive compare to normotensive. And there is also a significant correlation between blood pressure and lipid profile in prehypertensive subjects. Conclusion: Lipid profile is altered in prehypertensives compare to normotensives. That’s why timely diagnoses and life style modification is required in prehypertensives.